An unusual cause of fever and jaundice - Varyani, Umesh (Indian J Med Microbiol, 2021)
A 52 year old previously healthy woman from Mumbai presented with fever and jaundice of 10 days duration. At admission, she was jaundiced with tachycardia, tachypnea, hypoxia, hypotension, conjunctival congestion and mild erythematous flush over the skin. She had very high WBC counts and CRP's with direct hyperbilirubinemia and azotemia. Investigations for infectious causes of fever were negative. RT-PCR for SARS-CoV-2 in the nasopharynx was negative. However her SARS-CoV-2 antibodies were reactive. She also had echocardiographic and biochemical evidence of cardiac dysfunction. The diagnosis of Multisystem inflammatory syndrome–Adult (MIS-A) was thus established. She rapidly improved with intravenous immunoglobulin (2 gm/kg) and high dose steroids.